2019
DOI: 10.1017/s0007114519003143
|View full text |Cite
|
Sign up to set email alerts
|

Metabolically healthy general and abdominal obesity are associated with increased risk of hypertension

Abstract: Metabolically healthy obesity refers to a subset of obese people with a normal metabolic profile. We aimed to explore the association between metabolically healthy and obesity status and risk of hypertension among Chinese adults from The Rural Chinese Cohort Study. This prospective cohort study enrolled 9137 Chinese adults without hypertension, type 2 diabetes or treatment for lipid abnormality at baseline (2007–2008) and followed up during 2013–2014. Modified Poisson regression models were used to examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 36 publications
3
17
2
3
Order By: Relevance
“…We found that BMI and WC were positively associated with the risk of hypertension, findings that are consistent with those of some (but not all) previous studies 31–33. Some previous studies have not found overweight/obesity to be associated with hypertension,34 35 whereas our study did find positive associations and indicated that high WC had a more significant impact on the risk of hypertension than high BMI.…”
Section: Discussionsupporting
confidence: 92%
“…We found that BMI and WC were positively associated with the risk of hypertension, findings that are consistent with those of some (but not all) previous studies 31–33. Some previous studies have not found overweight/obesity to be associated with hypertension,34 35 whereas our study did find positive associations and indicated that high WC had a more significant impact on the risk of hypertension than high BMI.…”
Section: Discussionsupporting
confidence: 92%
“…3,5,6 Ser "o mais magro possível" dentro da faixa da normalidade do IMC pode ser a melhor sugestão com relação à prevenção primária da HA. 3,5,6,[32][33][34][35][36]…”
Section: Controle Do Peso (Gr: I; Ne: A)unclassified
“…[13]. The accumulation of abdominal fat is associated with the development of various disorders, such as atherogenic profile, arterial stiffness, elevated fibrinogen levels, hypertension, insulin resistance, hyperinsulinemia, glucose intolerance, arthritis, irregular menstruation, and gallbladder disorders [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Research shows that physical exercise can reverse part of these obesity-related pathologies by decreasing the availability of free fatty acids and improving the insulin sensitivity of glucose metabolism [29], reducing hypertension [30], decreasing arterial stiffness [31], reducing both fibrinogen and fibrinolytic biomarkers [32], relieving arthritis [33,34], and improving menstrual issues [35].…”
Section: Introductionmentioning
confidence: 99%